Pandanus martinianus (Pandanaceae), a new endemic species from northeastern India - Zanan, Rahul L.; Nadaf, Altafhusain B. (Phytotaxa, 2012)
A new species, Pandanus martinianus (Pandanaceae), from the foothills of West Siang District of Arunachal Pradesh and Dhimaji District of Assam of North-Eastern region of India is described and illustrated. The new taxon is distinguished from other Pandanus species by the dimensions and shape of its syncarp and the arrangement and shape of its drupes and stigmas. A discussion is provided of its morphological affinities, as well as a conservation assessment based on IUCN Red List Categories and Criteria.